Adding fun or function: Considering new product formulations for market expansion with a focus on hangover solutions. Issue 6 (3rd October 2022) - Park, Yeowoon; Lee, Dongmin; Jeong, Jaeseok; Moon, Junghoon
Abstract: This article aims to investigate the relationship between product formulations and consumers' willingness to buy (WTB), with the moderating role of the consumption situation. A 2 (utilitarian formulation vs. hedonic formulation) × 2 (unjustifiable situation vs. justifiable situation) between‐subjects design was constructed, and two specific formulations (pills and ice cream) were selected to represent a utilitarian formulation and hedonic formulation, respectively. Then, the hangover solution–consumption–situation was manipulated by varying drinking occasions. The results show that to strengthen the consumers' WTB a utilitarian product with such hedonic characteristics, consumers' justification process associated with hedonic consumption must be facilitated. This study is one of the first to address the notion that formulation differentiation can be a viable strategy in adding new features to a product. Practical Applications: Considering that the global health supplement market is growing, this study hopes to provide practitioners with useful insights regarding new product development for functional products. The findings of this study indicate that if companies aim to strengthen the WTB a utilitarian product with such hedonic characteristics, the justification process associated with hedonic consumption must be facilitated. For example, to boost sales, marketers can target specific days, such as Fridays or Saturdays, when consumers can more easily justify the hedonic consumption associated with drinking (i.e., drinking behavior, choosing a hangover solution product).